Revisiting the Daylit Area: Examining Daylighting Performance Using Subjective Human Evaluations and Simulated Compliance with the LEED Version 4 Daylight Credit. Issue 2 (3rd April 2017) - Nezamdoost, Amir; Van Den Wymelenberg, Kevin G.
ABSTRACT: The IES Lighting Measurement 83-12 Approved Method: IES Spatial Daylight Autonomy (sDA) and Annual Sunlight Exposure (ASE) (LM-83) codifies annual climate–based daylighting metrics and performance criteria, yet interpretation and application of the metrics and criteria are not fully substantiated. This article reports "daylit area" drawings prepared in the field by architecture students and compares these drawings to corresponding point-in-time and annual daylighting simulations. The point-in-time simulations without blinds showed less discrepancy between student daylit area evaluations than did annual simulations with blinds operated per LM-83. The daylit area drawings and point-in-time simulations together suggest a horizontal illuminance of 100 lx differentiating between non-daylit and partially daylit areas and 250 lx differentiating between partially and fully daylit areas. For 18 annual simulations that employed the LM-83 protocol, half were characterized similar to the field assessments. The other half consistently underpredicted daylight ratings; students found the spaces to be fully or partially daylit when the annual simulation predicted the spaces to be non-daylit. This study suggests that the spatial daylight autonomy (sDA) and ASE criteria in LM-83 may warrant refinement.